Pelatihan analisis SWOT untuk memahami kondisi internal dan eksternal - Djuli Sjafei Purba; Ridwin Purba; Tuahman Sipayung; Rosita Manawari Girsang; Marintan Saragih (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
The times have increased competition in all sectors of life. Along with the progress of the times, science also continues to grow. Knowledge is used to answer various human needs, increasingly fierce competition in organizations that require various strategies to survive and win the competition. SWOT analysis is one of the sciences used to produce this strategy (Strength=Strength, Weakness=Weakness, Opportunity=Opportunity, Threat=Threat). This analysis is to see the internal and external conditions of an organization. Likewise, the world of education, in this case, schools, needs to do a SWOT analysis to compete and have quality. The increasing number of schools will make the competition even more challenging, so the quality of schools must be crucial. This training activity aims to provide an understanding to the principal, functionaries, teachers, and employees of the importance of conducting a SWOT analysis and provide knowledge on how to conduct a SWOT analysis. This training activity lasted one day and was held in the GKPS 2 Pematangsiantar Private Vocational School building, which was attended by 15 participants from the Principal, Deputy Principal, Head of Department, Teachers, and Employees. The method used in implementing this activity is a lecture or material delivery and practice/training in conducting a SWOT analysis by taking the case of the GKPS 2 Pematangsiantar Private Vocational School. The results of this training activity showed there was an increase in the knowledge of the participants doing a SWOT analysis, as evidenced by the overall pre-test results from 43.3% to 61.3% of the overall post-test results from participants.